Associations of Body Dissatisfaction With Lifestyle Behaviors and Socio-Demographic Factors Among Saudi Females Attending Fitness Centers - Albawardi, Nada M.; AlTamimi, Abeer A.; AlMarzooqi, Mezna A.; Alrasheed, Lama; Al-Hazzaa, Hazzaa M. (Frontiers in Psychology, 2021)
Objective: To examine body image perception and the associations of body dissatisfaction (BD) with socio-demographic and lifestyle factors among Saudi women attending fitness centers in Riyadh. Methods: Saudi females aged 16 years and older were recruited from 12 randomly selected fitness centers in Riyadh, using stratified clustered sampling technique (n=460). Height and weight were measured to calculate actual BMI. A previously validated instrument was used to collect sociodemographic and lifestyle variables including physical activity (PA), sedentary behaviors, sleep and dietary habits. Stunkard Figure Rating Scale silhouettes were used to assess perceived and desired body shape. Results: The participants had a mean (SD) age of 29.2 (8.2). The majority were not married (57%), with no children (66%) and had college degrees (78%). While 63% were overweight or obese, nearly 40% of women underestimated their perceived body shape. The majority of respondents (87%) were dissatisfied with their body shape including 68% of normal weight women. Females who had BD were significantly older, had higher BMI, reported more weight loss attempt and had expended less time in vigorous (p= .033) and total (p= .042) PA than those who were satisfied with their body shape. However, when adjusting for socio-demographic variables, logistic regression analysis revealed significant associations of BD with higher BMI, shorter membership duration of fitness club, and reduced dairy products and energy drinks consumption. Conclusion: Except for BMI and decreased dairy products and energy drinks consumption, many lifestyle behaviors did not associate with BD among Saudi females attending fitness centers. The findings can inform healthcare providers when intervention strategy is implicated for females with BD. Future studies should compare the associations of BD with lifestyle behaviors between males and females attending fitness centers and seeking weight loss.